The impact of EGFR mutation and PD-L1 status on the efficacy of postoperative radiotherapy in stage III-pN2 NSCLC - Jinquan Yao; Yuxin Geng; Junhao Xu; Bingwen Zou; Feifei Teng (BMC Cancer)
Abstract Background The role of postoperative radiotherapy (PORT) for patients with completely resected stage III-pN2 non-small-cell lung cancer (NSCLC) remains controversial. PORT is not routinely recommended for patients with completely resected stage III-pN2 NSCLC. Therefore, identifying the population that could benefit from PORT is urgently needed. Methods We retrospectively enrolled 251 patients with completely resected stage III-pN2 NSCLC at our institution between 2018 and 2023. The Kaplan–Meier curves and log-rank tests were used to analyze disease-free survival (DFS) and overall survival (OS). Risk factors were identified using univariate and multivariate Cox regression analyses. The cumulative incidence rates of locoregional recurrence (LRR) were calculated via competing risk analyses and compared using the Gray test. Results A total of 251 patients were enrolled in the study, with the median follow-up of 24.9 months. Among overall patients, 61 patients underwent PORT, and 190 patients did not. Although patients in the PORT group exhibited a trend toward longer DFS, the difference was not statistically significant (median DFS: 39.1 vs. 35.5 months; HR 0.58, 95% CI 0.35–0.97; p = 0.072). Subgroup analyses revealed that PORT significantly prolonged DFS both in EGFR wild-type patients (median DFS: 35.3 vs. 18.3 months; HR 0.33, 95% CI 0.17–0.62; p = 0.002) and in PD-L1 positive patients (median DFS: 35.3 vs.16.4 months; HR 0.35, 95% CI 0.16–0.74; p = 0.029). In contrast, no significant DFS or OS benefits were observed in EGFR mutant patients or PD-L1 negative patients. Furthermore, PORT was associated with the significantly lower risk of LRR in overall patients (HR 0.39, 95% CI 0.16–0.97; p = 0.043), EGFR wild-type patients (HR 0.25, 95% CI 0.09–0.68; p = 0.007), and PD-L1 positive patients (HR 0.15, 95% CI 0.03–0.70; p = 0.016). PORT did not confer a locoregional control benefit in EGFR mutant patients (HR 0.58, 95% CI 0.07–4.58; p = 0.61) or PD-L1 negative patients (HR 1.02, 95% CI 0.27–3.82; p = 0.98). Conclusion For patients with completely resected stage III-pN2 NSCLC, PORT significantly improves DFS and reduces the risk of LRR in EGFR wild-type patients or PD-L1 positive patients. The EGFR and PD-L1 status may serve as biomarkers to identify the population that could benefit from PORT.